Exosome biopotentiated hydrogel restores damaged skeletal muscle in a porcine model of stress urinary incontinence - Tyler J. Rolland; Timothy E. Peterson; Ramandeep Takhter; Skylar A. Rizzo; Soulmaz Boroumand; Ao Shi; Tyra A. Witt; Mary Nagel; Cassandra K. Kisby; Sungjo Park; Lois A. Rowe; Christopher R. Paradise; et al. (npj Regenerative Medicine, 2022)
Abstract Urinary incontinence afflicts up to 40% of adult women in the United States. Stress urinary incontinence (SUI) accounts for approximately one-third of these cases, precipitating ~200,000 surgical procedures annually. Continence is maintained through the interplay of sub-urethral support and urethral sphincter coaptation, particularly during activities that increase intra-abdominal pressure. Currently, surgical correction of SUI focuses on the re-establishment of sub-urethral support. However, mesh-based repairs are associated with foreign body reactions and poor localized tissue healing, which leads to mesh exposure, prompting the pursuit of technologies that restore external urethral sphincter function and limit surgical risk. The present work utilizes a human platelet-derived CD41a and CD9 expressing extracellular vesicle product (PEP) enriched for NF-κB and PD-L1 and derived to ensure the preservation of lipid bilayer for enhanced stability and compatibility with hydrogel-based sustained delivery approaches. In vitro, the application of PEP to skeletal muscle satellite cells in vitro drove proliferation and differentiation in an NF-κB-dependent fashion, with full inhibition of impact on exposure to resveratrol. PEP biopotentiation of collagen-1 and fibrin glue hydrogel achieved sustained exosome release at 37 °C, creating an ultrastructural “bead on a string” pattern on scanning electron microscopy. Initial testing in a rodent model of latissimus dorsi injury documented activation of skeletal muscle proliferation of healing. In a porcine model of stress urinary incontinence, delivery of PEP-biopotentiated collagen-1 induced functional restoration of the external urethral sphincter. The histological evaluation found that sustained PEP release was associated with new skeletal muscle formation and polarization of local macrophages towards the regenerative M2 phenotype. The results provided herein serve as the first description of PEP-based biopotentiation of hydrogels implemented to restore skeletal muscle function and may serve as a promising approach for the nonsurgical management of SUI.